Menjadi Perempuan di Industri Kretek : Sebuah Studi Historiografi Gender dari Novel Gadis Kretek Karangan Ratih Kumala - Yunedi, Jefri; Naldi, Hendra (Jurnal Kronologi, 2025)
This research discusses Ratih Kumala's novel titled "Gadis Kretek" (Cigarette Girl) within a historiographical review of how Ratih presents her perspective on the status and roles of women in social life. The problems addressed in this novel are formulated as follows: (1) The influence of Ratih Kumala's background and the zeitgeist on the writing of the novel "Gadis Kretek." (2) The depiction and characteristics of female authorship by Ratih Kumala in the novel "Gadis Kretek." In this historiographical study, the research method applied is library research and is categorized as qualitative research. In library research, the study is focused and limited only to literature, as the name suggests. This research discusses the historical and cultural stigma surrounding femininity and the expectations placed on women. It also highlights how Dasiyah challenges patriarchal norms by engaging in activities traditionally associated with masculinity, such as kretek cigarette production. Ratih Kumala's work is positioned within a broader historical context, reflecting changing perceptions of women's rights and roles in society, particularly during the reformation era in Indonesia. This paper concludes that literature serves as an important tool for historians to understand social dynamics and the evolution of cultural norms regarding gender.